DEVELOPMENT AND EVALUATION OF MATERIALS FOR CHILDREN TO REDUCE THE TABLET DEVICE OPERATIONAL PROBLEMS: Received: 10th January 2022; Revised: 14th February 2022, 3rd March 2022, 5th March 2022; Accepted: 7th March 2022 - Kachi, Hodaka; Yasunaga, Taichi; Sakai, Kyohei; Hyuga, Ryosuke; Shiota, Shingo (PUPIL: International Journal of Teaching, Education and Learning, 2022)
In Japanese schools, there is a problem that teachers are overburdened. Therefore to reduce teachers’ workloads, this study developed online video teaching materials to assist students to troubleshoot their tablet device operational issues. To develop the teaching materials, we first conducted a questionnaire survey among teachers to understand what kind of operational problems were occurring with tablets in the classroom. We then developed the teaching materials based on the results. The evaluation of the teaching materials was conducted through questionnaires and interviews with teachers. The results suggested that the video teaching materials were able to resolve many of the students’ problems and reduce the need for the teachers to deal with all tablet device technical problems.